Keadilan dan Keterpercayaan Sistem Jual Beli Pre Order dalam Konteks Hukum Ekonomi Syariah - Wari, Nara Purnama (CV. Creative Tugu Pena, 2024)
This research aims to find out how fair and trustworthy the Pre Order buying and selling system is in the context of Sharia economic law. This research is library type research. The results of this research are: To ensure fairness and trust in pre-order buying and selling transactions, certainty and guarantees are needed for both parties. The buyer must be sure that the goods ordered will be delivered according to the agreed time and conditions, while the seller needs assurance that the buyer will make payment according to the agreement through: 1) Compliance with Sharia Principles. 2) Limitation of Usury, 3) Prevention of Gharar, 4) Prohibition of Maysir, 5) Justice and Equality, 6) Compliance with Sharia Principles, 7) Commitment to Common Interests. Keywords: Pre-Order Buying and Selling, Justice of the Buying and Selling System